Status of nutrition-relevant interventions during pregnancy in India: Insights from the National Family Health Survey-4 - Avula, Rasmi; Sarswat, Esha; Chakrabarti, Suman; Mani, Sneha; Nguyen, Phuong Hong; Menon, Purnima (International Food Policy Research Institute, 2018)
The World Health Organization antenatal care guidelines 2016 have emphasized maternal nutrition assessment and provision of a set of nutrition-relevant interventions. This Data Note describes the current levels of key maternal nutrition interventions during pregnancy, summarizing the National Family Health Survey-4 (2016) data from 640 districts of India.